On the dynamics of matching between issuers and reputable underwriters in the chinese international bond market - Yuexia Li; Tai-Hu Ling; Ricky Chee Jiun Chia (Journal of Propulsion Technology, 2024)
We analyse employments of reputable underwriters in China of providing services in cross-border international bond offerings. Numerous previous studies have highlighted the important role of underwriter reputation in determining the successes of issuance. Bonds underwritten by reputable underwriters are considered ‘trustworthy’ or ‘safe’ by prospective investors, and hence the higher the reputation of the underwriters the more the investors will trust the information disclosed and the quality of the issuance. This study also examines the potential important determinants and will contribute to a better understanding of the Chinese international debt market in particular and the Chinese capital market in general